A Network Model for Human Interoperability. (March 2014) - Handley, Holly A. H.
Objective: The objective is to demonstrate how the Human View architecture can be used to define and evaluate the human interoperability capabilities of a net-centric system. Human interoperability strives to understand the types of system relationships that affect collaboration across networked environments. Background: The Human View was developed as an additional system architectural viewpoint to focus on the human component of a system by capturing data on human roles, tasks, constraints, interactions, and metrics. This framework can be used to collect and organize social system parameters to facilitate the way that humans interact across organizational boundaries. Method: By mapping the Human View elements to organizational relationships defined in the domain of network theory, a network model of the Human View can be developed. This representation can then be aligned with a Layers of Interoperability model for collaborative systems. The model extends traditional technical interoperability to include organizational aspects important for human interoperability. The resulting composite model can be used to evaluate the human interoperability capability of network-enabled systems. Results: An interagency response to a crisis situation is an example where increased levels of human interoperability can affect the effectiveness of the organizational interactions. The existing Human View products representing the interagency capabilities were evaluated using the network model to demonstrate how the social system variables can be identified and evaluated to improve the system design. Conclusion: By understanding and incorporating human interoperability requirements, the resulting system design can more effectively support collaborative tasks across technological environments to facilitate timely responses to events.